Transporters in drug delivery - Shende, Pravin (Henry Stewart Talks, 2022)
Biotransporters in drug delivery, Classification of transporters, P-glycoprotein transporters, Transporters for cancer therapy, Solute carrier transporters, Facilitative glucose transporters, The substrates and inhibitors of different transporters, Effect of transporters in drug delivery, Pharmacological applications